PKM :KERIPIK PISANG ANEKA RASA - Juliannisa, Indri Arrafi; Siswantini, Tri (IKRA-ITH ABDIMAS, 2020)
In June 2019, the Jakarta community service team conducted a study and provided community service to the residents of Bojongcae Village, Lebak Regency, Banten Province about education and skills that can improve the quality of self and become additional sources of family income. Based on the results of previous studies that the Bojongcae Village has the potential of agricultural products, like a banana fruit. All this time, if the banana is harvested, so directly sell to the market, but not all of thebanana is sold out on the market, therefore it is better to add a higher added value to the banana product, then the community service team made training to make chips made from bananas. Although the co-19 pandemic, this community service activity was still carried out, and for the result is the partner group of Bojongcae Village has been able to produce banana chips with original flavors, sweet and spicy, onion chicken and sweet corn, with this entrepreneurial activity can increase the income of the partner group.